The Effect of Work Environment and Work Motivation on Employee Performance of PT Pegadaian Manado Selatan Branch - Lumantow, Claudia Gabriella; Pio, Riane Johnly; Mukuan, Danny D. S. (Productivity, 2024)
The purpose of this research is to determine the influence of the work environment and work motivation on employee performance at PT. Pawnshop South Manado Branch. This method uses multiple linear regression analysis. The sample used was 50 respondents using the Saturated Sampling Method. The results of the t test research show that the Work Environment coefficient value is -1.869 < 2.012 with the calculated t value less than the t table while the significance level is 0.495 > 0.005, partially indicating that the Work Environment has no significant influence on Employee Performance and the Work Motivation coefficient value is 3.350 and > 2.012 With a calculated t value > t table while the significance level is 0.002 < 0.005, it shows that it partially has a significant effect on employee performance. Keywords: Work Environment, Work Motivation, Employee Performance